Features of distance learning of university students in the context of digitalization - Limarenko Olga; Dergach Elena; Kokhan Sergey; Romanova Svetlana; Nadeina Luiza (E3S Web of Conferences, 2021)
This article is devoted to special aspects of giving classes in the discipline “Applied Physical Education and Sports” at the Department of Physical Culture at Siberian Federal University. These aspects are considered an example of development and introduction of online course of the swimming specialization in educational process. It is connected with the transition to distance learning caused by the spread of COVID-19 infection in the world. The transition to this format of study was an effective way of interacting with full-time students in the applied discipline. It made it possible to avoid the eventual interruption of educational activities, as feedback from the “student – university teacher” was organized. This allowed the students to receive the full information by providing interim assessment for the spring semester of the 2019-2020 academic year. The article reflects the personal experience of university teachers in the development and implementation of the electronic course, its main resources, content, and features of functioning. This allowed asynchronously teach students, posting interactive lectures, offer videos on the topic of the course, issue practical tasks and training programs, check the assimilation of material, as well as monitor the performance of tasks, maintain motor activity and health of students.